Quality of Life Among Patients with Diabetes Mellitus Receiving Insulin Therapy - Imelda Sirait; Adriani Natalia M; Juwita Moreen Toar (An Idea Nursing Journal, 2026)
Abstract: Diabetes Mellitus (DM) is a chronic disease with a continuously increasing prevalence both globally and nationally. Patients with DM who undergo insulin therapy often face various challenges—physical, psychological, and social—that may affect their quality of life. This study aims to describe the quality of life of patients with DM who use insulin.This study employed a descriptive qualitative design with a total of 108 respondents. The respondents’ characteristics included age, educational level, duration of illness, and gender. Quality of life was measured based on physical, psychological, and social dimensions.The results showed that the majority of respondents were aged 19–59 years (76.9%), had a senior high school education (39.8%), had been diagnosed with DM for less than one year (56.5%), and were female (74.1%). Most respondents had a moderate quality of life (97.2%), while only 2.8% had a good quality of life.These findings indicate that although insulin therapy is the primary treatment in DM management, patients’ quality of life remains suboptimal. Factors such as productive age, early stage of the disease, and female predominance contribute to this condition. In addition, psychological aspects such as diabetes-related distress and social limitations also influence patients’ quality of life. In conclusion, the quality of life of patients with DM using insulin is influenced by the interaction of biological, psychological, and social factors. Therefore, comprehensive and holistic nursing interventions are required, including self-management education, psychological support, and strengthening family support to improve patients’ quality of life.